Pengaruh waiting time pre anestesi terhadap tingkat kecemasan pasien pre operasi - Kaharudin, Endang; Futriani, Elfira Sri (Holistik Jurnal Kesehatan, 2025)
Background: Long waiting times before anesthesia often exacerbate patient anxiety, as they have more time to think about the risks and potential complications. The impact of prolonged waiting time increases the risk of dehydration due to fasting, changes in patient condition, increased anxiety, and patient discomfort. Purpose: To determine the effect of pre-anesthesia waiting time on the anxiety level of pre-operative patients. Method: Quantitative research, using the cross sectional method, was carried out at Karawang Regional General Hospital in November 2024 - January 2025. The sampling technique used purposive sampling with the number of samples used as many as 87 respondents. The independent variable in this study was preoperative waiting time, while the dependent variable was anxiety level. Data analysis used univariate in the form of frequency distribution and bivariate using Spearman Rank. Results: The correlation between waiting time and anxiety level was significant (p=0.000, r=0.854). The value of r contains a positive relationship that is if the long waiting time for surgery will cause anxiety. Conclusion: Anesthesia, long waiting time, and lack of medical information increase the anxiety of pre-operative patients and their families. Adequate education is needed to reduce anxiety and improve family readiness.   Keywords: Anxiety; Pre-Anesthesia; Waiting Time.   Pendahuluan: Waktu tunggu yang lama sebelum tindakan anestesi seringkali memperburuk kecemasan pasien, karena mereka memiliki lebih banyak waktu untuk memikirkan risiko dan kemungkinan komplikasi. Dampak waiting time yang panjang meningkatkan risiko dehidrasi karena puasa, perubahan kondisi pasien, peningkatan kecemasan, dan ketidaknyamanan pasien. Tujuan: Untuk mengetahui pengaruh waiting time pre anestesi terhadap tingkat kecemasan pasien pre-operasi. Metode: Penelitian kuantitatif, menggunakan metode cross sectional, dilaksanakan di Rumah Sakit Umum Daerah Karawang pada bulan November 2024 - Januari 2025. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel yang digunakan sebanyak 87 responden. Variabel independen dalam penelitian ini adalah waiting time pre operasi, sedangkan variabel dependen adalah tingkat kecemasan. Analisis data yang digunakan univariat dalam bentuk distribusi frekuensi dan bivariat menggunakan Spearman Rank. Hasil: Menunjukkan korelasi lama waktu tunggu dan tingkat kecemasan memiliki hubungan yang signifikan (p=0.000, r=0.854). Nilai r mengandung hubungan yang positif, yaitu jika lamanya waktu tunggu operasi dapat menimbulkan kecemasan. Simpulan: Anestesi, waktu tunggu lama, dan kurangnya informasi medis meningkatkan kecemasan pasien pre-operasi dan keluarganya. Edukasi yang memadai diperlukan untuk mengurangi kecemasan dan meningkatkan kesiapan keluarga.   Kata Kunci: Kecemasan; Pre-Anestesi; Waiting Time.